Komunikasi Publik Bagian Protokol Komunikasi Pimpinan Sekretariat Daerah Kota Cirebon: Analisis Konten Kualitatif Melalui Model Philipp Mayring Pada Akun Instagram @Prokompimkotacirebon - Rahim, Anisha Febri; Koswara, Aang; Nugraha, Aat Ruchiat (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study was motivated by the phenomenon of a significant increase in content upload activity on the Instagram account @prokompimkotacirebon during 2024, which contrasted with a decline in followers compared to previous years. This raised questions about the effectiveness of public communication conducted by the Protocol and Communication Section of the Regional Secretariat of Cirebon City in attracting attention and building public engagement. This phenomenon raises questions about the quality of content as public communication conducted by the Protokol dan Komunikasi Pimpinan (Prokompim) of the Regional Secretariat of Cirebon City in attracting attention and fostering public engagement. The study employed a qualitative method using Philipp Mayring's qualitative content analysis model. Data were collected through an in-depth analysis of 297 posts in the form of images, videos, and infographics; and structured interviews with five informants from Prokompim Kota Cirebon. The findings revealed that the posts on the Instagram account @prokompimkotacirebon predominantly focused on delivering information about leadership involvement in various formal and informal events. Video formats demonstrated the highest engagement levels as they integrated visually appealing elements, text, and audio. Additionally, cross-sectoral collaborations with government institutions, communities, and public figures contributed to broader message outreach and increased information credibility. The study also identified several challenges, such as the lack of Standard Operating Procedures (SOPs) in content management, low interactivity in communication within posts, and human resource limitations affecting message delivery consistency during strategic hours.